Quantitative Factors of Production Parameters Affecting Broiler Performance Index - Akbar Satria Bahari; Novie Andri Setianto; Yusmi Nur Wakhidati; Elly Tugiyanti; Rahayu Widiyanti (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2026)
This study aims to analyze the effects of quantitative production parameters on the Performance Index (PI) of broiler chickens. Five key variables were examined: mortality, culling, feed conversion ratio (FCR), final body weight, and harvesting age. The analysis utilized secondary historical data from 17 production cycles of broiler chickens at PT XYZ between 2021 and 2023. Multiple linear regression was employed after satisfying classical assumption tests. Results indicate that all independent variables significantly influenced PI both simultaneously (p < 0.05) and partially. The adjusted R-squared value of 99.81% demonstrates that the model explains nearly all variation in the performance index. Partially, final body weight had the highest positive impact on PI (coefficient +223.11), followed by FCR (-184.84), harvesting age (-10.41), culling (-3.61), and mortality (-3.238), all with negative effects. These findings highlight the critical role of production parameter control in optimizing broiler performance efficiency.